1987
DOI: 10.2307/1591034
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Hematologic, Endocrine, and Clinical Chemistry Values in Ducks and Roosters

Abstract: Venous blood samples were collected at 3-day intervals for a total of six samples from each of five adult male pekin ducks and five adult Ross roosters. Twenty biochemical, six hematologic, and three endocrine determinations were performed on each blood or serum sample collected. The data obtained provide reference values for future studies of avian species and illustrate the utility of an automated clinical chemistry analyzer in assessing multiple serum biochemistry values in small sample volumes obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
2
11
0
4
Order By: Relevance
“…A conventionally accepted reference range for CK is between 100 and 500 IU/L (Thrall, 2004), which was exceeded as early as at the immediate post-hatch state. This may be a result of the one-sided selection for muscle mass production, as a highly similar trend was described in meat-type turkeys (Szabó et al, 2005) and roosters (Spano et al, 1987), while wild-living birds, e.g. starlings (Juráni et al, 2004) were not characterised by such high values, only migrating species, e.g.…”
Section: Plasma Enzymessupporting
confidence: 58%
“…A conventionally accepted reference range for CK is between 100 and 500 IU/L (Thrall, 2004), which was exceeded as early as at the immediate post-hatch state. This may be a result of the one-sided selection for muscle mass production, as a highly similar trend was described in meat-type turkeys (Szabó et al, 2005) and roosters (Spano et al, 1987), while wild-living birds, e.g. starlings (Juráni et al, 2004) were not characterised by such high values, only migrating species, e.g.…”
Section: Plasma Enzymessupporting
confidence: 58%
“…During the entire trial the control chicken remained alert and active and showed no signs of disease. All blood counts and serum chemistry results were within normal limits for chickens (Spano et al, 1987;Canadian Council on Animal Care, 1993;Bounous and Stedman, 2000) and did not differ from the negative control chickens.…”
Section: Chicken Trialmentioning
confidence: 72%
“…The mean total thrombocyte count in native Iranian ducks (31.5i1.8 x103/pl) was also within the limits (Coles and Campbell, 1986). Similarly mean WBC counts in both sexes were as in other ducks (Spano et al, 1987) though lower than their Indian counterparts (Sreeraman et al, 1979).…”
Section: Resultsmentioning
confidence: 68%
“…Res. 0971-2119/96/$05.00 0 GSP, India Pitts 1976;Sreeraman et al, 1979;Driver, 1981;Spano et al, 1987;Hebert, 1989 andBhattacharyya et al, 1991). Since no information appears to be available on the hematological values in Iranian native ducks, this study has been conducted.…”
Section: Introductionmentioning
confidence: 99%